Interfacing biology with nanoparticles - Mandal, Sujata; Phadtare, S.; Sastry, M. (Current Applied Physics, 2005)
New approaches are constantly being developed for both the synthesis of inorganic nanomaterials and their surface modification for sensing and electronic applications. Insofar as surface modification of gold nanoparticles is concerned, thiol chemistry is the most popular approach to bind ligands to their surface. We have been pursuing the possibility of using amine functionality to bind ligands to the surface of gold nanoparticles and have found that amine binding is as strong as thiol binding. The advantages of using amine chemistry for surface modification of nanogold are many, the possibility of complexing a large variety of biomolecules such as amino acids and proteins being one of the most important. In this article, we review the work from this laboratory on the stabilization of gold nanoparticles using amino acids as well as using amino acids as reducing agents to obtain stable aqueous solutions of gold nanoparticles of variable size. We also discuss the possibility of forming bioconjugates of enzymes with gold nanoparticles decorating the surface of polymer microspheres and their application as reusable biocatalysts. There is much to be gained by marrying nanomaterials with biology with considerable spin-offs likely in both nanotechnology and biotechnology. (C) 2004 Elsevier B.V. All rights reserved.
Indo-Japan Workshop on Advanced Molecular Electronics and Bionics, Kyushu Inst Technol, Grad Sch Life Sci & Syst Engn, Kitakyushu, JAPAN, DEC 11-13, 2003
Keywords: amino acids' enzyme immobilization; Nanoparticles; Proteins